Sustainable Conservation of Malay Traditional Architecture East Sumatera Indonesia - Andriana, Melly; Marpaung, B O Y; Nasution, Achmad Delianur; Fachrudin, Hilma Tamiami (International Journal of Architecture and Urbanism, 2025)
Over time, physical and non-physical changes can affect the existence of Traditional buildings. The current phenomenon begins with a social shift in society that is inseparable from the influence of several factors. First, advances in communication technology make humans live in practicality. Second, is the influence of foreign cultures (Westernization). Building conservation can be an option in maintaining and improving the preservation of Traditional Buildings by paying attention to the usefulness, social function, and cultural meaning behind the pattern or style of the building. This study aims to determine the existence of Malay Traditional Buildings and Houses that have decreased conditions and even are almost extinct, so it is necessary to carry out sustainable conservation to maintain the existence of buildings or improve building conditions. The variables raised relating to the approach of aspects that influence the decision to conserve traditional buildings are; classification of structures, construction philosophy (ethics, thinking, existence, time, meaning, and value), the structural strength of the material, material components, the concept of preservation, and community empowerment. The research location is the Malay Traditional Building in East Sumatra, Serdang Bedagai Regency, which is still lived by the owner or his relatives. Research data consists of resources that exist at the research site, both physical data and non-physical data. First, physical data is obtained through the existence of Traditional buildings along with building components. Second, non-physical data can be known through local people's knowledge of culture in development to get supporting factors for conservation. The analysis is carried out using descriptive qualitative methods. Data was collected with literature reviews, interviews, and observations at several Traditional Building locations to obtain data on Traditional buildings. The discovery will result in how much influence these supporting factors have on preserving Traditional Houses, especially in East Sumatra, Indonesia.